Effects of Provenance, Growing Site, and Growth on Quercus robur Wood Anatomy and Density in a 12-Year-Old Provenance Trial - Hietz, Peter; Rungwattana, Kanin; Scheffknecht, Susanne; George, Jan-Peter (Frontiers in Plant Science, 2022)
Vessels are responsible for an efficient and safe water transport in angiosperm xylem. Whereas large vessels efficiently conduct the bulk of water, small vessels might be important under drought stress or after winter when large vessels are embolized. Wood anatomy can adjust to the environment by plastic adaptation, but is also modified by genetic selection, which can be driven by climate or other factors. To distinguish between plastic and genetic components on wood anatomy, we used a Quercus robur trial where trees from ten Central European provenances were planted in three locations in Austria along a rainfall gradient. Because wood anatomy also adjusts to tree size and in ring-porous species, the vessel size depends on the amount of latewood and thereby ring width, we included tree size and ring width in the analysis. We found that the trees’ provenance had a significant effect on average vessel area (VA), theoretical specific hydraulic conductivity (Ks), and the vessel fraction (VF), but correlations with annual rainfall of provenances were at best weak. The trial site had a strong effect on growth (ring width, RW), which increased from the driest to the wettest site and wood density (WD), which increased from wet to dry sites. Significant site x provenance interactions were seen only for WD. Surprisingly, the drier site had higher VA, higher VF, and higher Ks. This, however, is mainly a result of greater RW and thus a greater proportion of latewood in the wetter forest. The average size of vessels > 70 μm diameter increased with rainfall. We argue that Ks, which is measured per cross-sectional area, is not an ideal parameter to compare the capacity of ring-porous trees to supply leaves with water. Small vessels (<70 μm) on average contributed only 1.4% to Ks, and we found no evidence that their number or size was adaptive to aridity. RW and tree size had strong effect on all vessel parameters, likely via the greater proportion of latewood in wide rings. This should be accounted for when searching for wood anatomical adaptations to the environment.